2018
DOI: 10.1002/jor.24106
|View full text |Cite
|
Sign up to set email alerts
|

Transforming growth factor β mediates communication of co‐cultured human nucleus pulposus cells and mesenchymal stem cells

Abstract: Intervertebral disc (IVD) consists of surrounding tissue annulus fibrosus and central nucleus pulposus, which are partially degenerative in scoliotic IVDs. Successful regeneration of scoliotic alterations requires cognition of critical paracrine mediators of cell-to-cell contact in the IVD. In this work, we hypothesized that transforming growth factor β (TGF-β) is involved in the intercellular communication of nucleus pulposus cells (NPCs) and mesenchymal stem cells (MSCs). We observed that in cultured NPCs TG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 37 publications
0
11
0
Order By: Relevance
“…Next, we analyzed the expression of genes related to the pathways targeted by each of the small molecules (S, Da, De and F) at day 5 of myotube differentiation. As shown in Figure 2—figure supplement 2A–D, we found significant differential expression of CEBPD and FKBP5 (De targets; Luedi et al, 2017; MacDougald et al, 1994; Pan et al, 2010; Pereira et al, 2014; Reddy et al, 2012; Scharf et al, 2011), HES1 and NOTCH2 (Da targets; Huang et al, 2011; Jarriault et al, 1995; Mao et al, 2018), COL1A1 and ID3 (S targets; Lehmann et al, 2018; Ramachandran et al, 2018; Sato et al, 2015) and PPARGC1A (F target; Charos et al, 2012; Martin et al, 2009; Sayasith et al, 2014). Of note, S/Da/De/F treatment also induced the maturation of PS cell-derived myotubes generated under transgene-free conditions (Xi et al, 2017) (Figure 2—figure supplement 3A–B).…”
Section: Resultsmentioning
confidence: 52%
“…Next, we analyzed the expression of genes related to the pathways targeted by each of the small molecules (S, Da, De and F) at day 5 of myotube differentiation. As shown in Figure 2—figure supplement 2A–D, we found significant differential expression of CEBPD and FKBP5 (De targets; Luedi et al, 2017; MacDougald et al, 1994; Pan et al, 2010; Pereira et al, 2014; Reddy et al, 2012; Scharf et al, 2011), HES1 and NOTCH2 (Da targets; Huang et al, 2011; Jarriault et al, 1995; Mao et al, 2018), COL1A1 and ID3 (S targets; Lehmann et al, 2018; Ramachandran et al, 2018; Sato et al, 2015) and PPARGC1A (F target; Charos et al, 2012; Martin et al, 2009; Sayasith et al, 2014). Of note, S/Da/De/F treatment also induced the maturation of PS cell-derived myotubes generated under transgene-free conditions (Xi et al, 2017) (Figure 2—figure supplement 3A–B).…”
Section: Resultsmentioning
confidence: 52%
“…But in order to better understand the physiology and function of the NPlike cells, the cells should be evaluated by specific NP phenotypic markers, in accordance with the consensus stated by The Spine Research Interest Group at the 2014 Annual ORS Meeting 114 . On the other hand, TGF-b mediates the communication between NPCs and MSCs, which can improve the quality of IVD cells and promote the regeneration of degenerated IVD tissue 115 . Furthermore, with the development of various biomaterials, such as injectable hydrogels and self-assembling polypeptide scaffolds, the TGF-b can be released slowly to stimulate the TGF-b-induced MSCs differentiation and drive the MSCs-mediated IVD regeneration process 116e118 .…”
Section: The Treatment Prospect Of Tgf-b Signaling In Ivd Degenerationmentioning
confidence: 99%
“…It binds to collagen, forms part of the extracellular matrix (ECM), and interacts with integrins on cell surfaces. The study showed that TGF-β increased the expression of COL1A1, ACAN, and SOX9 genes by mediating communication between nucleus pulposus cells and mesenchymal stem cells [43]. Activation of TGF-β signaling has a protective effect on the intervertebral disc via inhibition of ECM degradation and increase of ECM synthesis, promotion of cell proliferation and inhibition of cell death, and alleviation of inflammatory response.…”
Section: Discussionmentioning
confidence: 97%